Case Report: Resolution of radiation pneumonitis with androgens and growth hormone - Yen, Allen; Westover, Kenneth D. (Frontiers in Oncology, 2022)
Background: Radiation pneumonitis (RP) occurs in some patients treated with thoracic radiation therapy. RP often self-resolves, but when severe it is most commonly treated with corticosteroids because of their anti-inflammatory properties. Androgens and human growth hormone (HGH) also have anti-inflammatory and healing properties in the lung, but have not been studied as a remedy for RP. Here we present a case of corticosteroid-refractory RP that resolved with androgen and HGH-based therapy. Case Presentation: A 62 year old male body builder with excellent performance status presented with locally advanced non-small cell lung cancer characterized by a 7 cm mass in the right lower lobe and associated right hilar and subcarinal lymph node involvement. He was treated with chemoradiation and an excellent tumor response was observed. However, 2 months post-treatment he developed severe shortness of breath and imaging was consistent with RP. His RP was refractory to prednisone and antibiotic therapy, despite various regimens over a 9 month period. The patient self-treated with an androgen and HGH-based regimen and the RP promptly resolved. Conclusion: The anti-inflammatory properties of androgens and HGH have prompted an exploration of their potential role in therapeutic strategies to treat pro-inflammatory conditions such as sepsis, infections and interstitial lung disease. This case study suggests a potential role for the use of androgens for the treatment of steroid-refractory RP after radiation therapy. However, the applicability of this strategy to general populations should be weighed carefully against secondary effects of these agents, especially in the setting of cancer survivorship.